Sensory discriminability of older consumers: Interaction between evaluation method, number of samples, and age-related characteristics - Su Yun Lim; Mi-Ran Kim (Food Research International, 2026)

Application of insect oils in bone broth: Effects of roasting and ultrasound-assisted extraction on meat-like volatiles, fatty acid profile and sensory properties - Jin-Kyung Nam; Yu-Jeong Han; Mi-Ran Kim; Jeong Eun Hyeon; Hae Won Jang (Food Chemistry, 2026)

Enhanced cycling stability of black electrochromic device with hydroquinonesulfonate salt as an efficient redox mediator for energy-saving windows - Xiaojing Lv; Rongxiang Chen; Ran Cheng; Juncheng Dong; Jin Li; Hongzheng Chen; Grigory Kim; Alexey Tameev; Alexander Nekrasov; Mi Ouyang; Cheng Zhang (Chemical Engineering Journal, 2026)

Roasting-induced modulation of volatile profiles and sensory attributes in edible insect oils - You Rim Min; Mi-Ran Kim; Hae Won Jang (Food Research International, 2026)

Influence of the drying method on the physicochemical properties, volatile compounds, and odor characteristics of edible insect oils - Ji Yoon Cha; Mi-Ran Kim; Yea-Ji Kim; Jeong Heon Kim; Jaejoon Han; Yun-Sang Choi (Food Research International, 2025)

Multistrain Probiotics Alleviate Diarrhea by Modulating Microbiome-Derived Metabolites and Serotonin Pathway - Jin-Ju Jeong; Yoo-Jeong Jin; Raja Ganesan; Hee Jin Park; Byeong Hyun Min; Min Kyo Jeong; Sang Jun Yoon; Mi Ran Choi; Satya Priya Sharma; You Jin Jang; Uigi Min; Jong-Hyun Lim; et al. (Probiotics and Antimicrobial Proteins, 2025)
Diarrhea, a common gastrointestinal symptom in health problems, is highly associated with gut dysbiosis. The purpose of this study is to demonstrate the effect of multistrain probiotics (Sensi-Biome) on diarrhea from the perspective of the microbiome-neuron axis. Sensi-Biome ( Lactiplantibacillus plantarum , Bifidobacterium animalis subsp. lactis , Lactobacillus acidophilus , Streptococcus thermophilus , Bifidobacterium bifidum , and Lactococcus lactis ) was administered in a 4% acetic acid–induced diarrhea rat model at concentrations of 1 × 10 8 (G1), 1 × 10 9 (G2), and 1 × 10 10 CFU/0.5 mL (G3). Diarrhea-related parameters, inflammation-related cytokines, and stool microbiota analysis by 16S rRNA were evaluated. A targeted and untargeted metabolomics approach was used to analyze the cecum samples using liquid chromatography and orbitrap mass spectrometry. The stool moisture content ( p < 0.001), intestinal movement rate ( p < 0.05), and pH ( p < 0.05) were significantly recovered in G3. Serotonin levels were decreased in the multistrain probiotics groups. The inflammatory cytokines, serotonin, and tryptophan hydroxylase expression were improved in the Sensi-Biome groups. At the phylum level, Sensi-Biome showed the highest relative abundance of Firmicutes . Short-chain fatty acids including butyrate, iso-butyrate, propionate, and iso-valeric acid were significantly modified in the Sensi-Biome groups. Equol and oleamide were significantly improved in the multistrain probiotics groups. In conclusion, Sensi-Biome effectively controls diarrhea by modulating metabolites and the serotonin pathway.

Physicochemical characterization and in vivo assessment of novel apixaban-loaded polymeric nano-aggregates - Fakhar ud Din; Hye In Lee; Jung Suk Kim; Mi Ran Woo; Seunghyun Cheon; Seonghyeon Park; Sanghyun Woo; Sung Giu Jin; Han-Gon Choi (Journal of Pharmaceutical Investigation, 2025)

Development of a novel apixaban-loaded solid self-emulsifying drug delivery system for oral administration: physicochemical characterization and pharmacokinetics in rats - Hye In Lee; Mi Ran Woo; Fakhar ud Din; Jung Suk Kim; Seunghyun Cheon; Seonghyeon Park; Sanghyun Woo; Sung Giu Jin; Han-Gon Choi (Journal of Pharmaceutical Investigation, 2025)

Impact of thawing methods and packaging sizes on the physicochemical and microbial quality of frozen kimchi - Hee Eun Kim; Yun-Jeong Choi; Dong Hyun Park; Min Jung Lee; Minji Kim; Sung Jin Park; Ji Young Choi; Mi Ran Kang; Sung Hee Park; Mi-Ai Lee (International Journal of Refrigeration, 2025)

Quinine inhibits myogenic differentiation by disrupting AKT signaling pathway - Mi Ran Byun; Sou Hyun Kim; RanJu Woo; Seung Jun Noh; Sang Hoon Joo; Young-Suk Jung; Joon-Seok Choi (Toxicological Research, 2025)

Deciphering the links: Fragmented polystyrene as a driver of skin inflammation - Gyeong Bae Song; Jisoo Nam; Sangmin Ji; Gijeong Woo; Soojeong Park; Bokyung Kim; Jeein Hong; Myung Gil Choi; Seokheon Kim; Chaerin Lee; Wonchul Lim; Sangwoon Yoon; et al. (Journal of Hazardous Materials, 2024)

Variation of volatile compounds and sensory profile for Protaetia brevitarsis larvae fermented with lactic acid bacteria and yeast - Ji Yoon Cha; Jaejoon Han; JeongAe Heo; Hwan Hee Yu; Yea-Ji Kim; Hae Won Jang; Mi-Ran Kim; Yun-Sang Choi (Food Chemistry, 2024)

Consumer-driven characterization of healing foods using Q methodology and Q based sorting - Ki-Beom Song; Sébastien Lê; Haeng-Ran Kim; Seon-Mi Yoo; Min-Sook Kang; Han-Na Chu; In-Seon Hwang; Jae-Hee Hong (Food Quality and Preference, 2024)

Hydroprocessing characteristics of palm fatty acid distillate in palm oil into low-carbon biofuel - Soo Hyun Kim; Hyerim Ko; Mi Ran Lee; Jin-Kuk Kim; Young-Woong Suh (Fuel, 2024)

Novel rivaroxaban-loaded microsphere systems with different surface microstructure for enhanced oral bioavailability - Min-Jong Choi; Mi Ran Woo; Kyungho Baek; Jung Suk Kim; Jong Oh Kim; Yong Seok Choi; Han-Gon Choi; Sung Giu Jin (Drug Delivery and Translational Research, 2024)

Relationship between PM1.0 and PM2.5 in urban and background areas of Republic of Korea - Sujin Kwon; Soo Ran Won; Hyung Bae Lim; Sung Chul Hong; Yong Mi Lee; Ji Yun Jung; Sung-Deuk Choi; Sang-Jin Lee; Seungmee Oh; Ju Young Kim; Yong Pyo Kim; Hye Jung Shin; et al. (Atmospheric Pollution Research, 2023)

Comparison of descriptive analysis and flash profile by naïve consumers and experts on commercial milk and yogurt products - JeongAe Heo; Se Jin Lee; Jungmin Oh; Mi-Ran Kim; Han Sub Kwak (Food Quality and Preference, 2023)

Comparison of sensory profiles by two different check-all-that-apply (CATA) terms developed from trained panelists and naïve consumers - Mi-Ran Kim; JeongAe Heo; Han Sub Kwak (Food Quality and Preference, 2023)

Establishment of a qualified ex vitro-acclimatized whole plant reproduction system using secondary somatic embryos in Panax ginseng - Ju Hee Kim; Mi Young Kim; Jae Hyun Lee; Jang Uk Kim; Ok Ran Lee (Plant Biotechnology Reports, 2023)

Multiple low-dose radiation-induced neuronal cysteine transporter expression and oxidative stress are rescued by N-acetylcysteine in neuronal SH-SY5Y cells - Ji-Young Yoo; Ye-Ji Lee; Yu-Jin Kim; Tai-Kyoung Baik; Jun-Ho Lee; Mi‑Jo Lee; Ran-Sook Woo (NeuroToxicology, 2023)

Anti-apoptotic Splicing Variant of AIMP2 Recover Mutant SOD1-Induced Neuronal Cell Death - Myung Geun Kook; Mi Ran Byun; Soo Min Lee; Min Hak Lee; Dae Hoon Lee; Hyung Been Lee; Eui-Jin Lee; Kyunghwa Baek; Sunghoon Kim; Kyung-Sun Kang; Jin Woo Choi (Molecular Neurobiology, 2023)

Correction to: Genetic diversity and evolutionary history of Korean isolates of severe fever with thrombocytopenia syndrome virus from 2013–2016 - Mi-ran Yun; Jungsang Ryou; Wooyoung Choi; Joo-Yeon Lee; Sun-Whan Park; Dae-Won Kim (Archives of Virology, 2020)
Authors would like to correct the 4th author name from “Ju-Yeon Lee” to the correct version “Joo-Yeon Lee”.

Genetic diversity and evolutionary history of Korean isolates of severe fever with thrombocytopenia syndrome virus from 2013–2016 - Mi-ran Yun; Jungsang Ryou; Wooyoung Choi; Joo-Yeon Lee; Sun-Whan Park; Dae-Won Kim (Archives of Virology, 2020)
Severe fever with thrombocytopenia syndrome (SFTS) is caused by SFTS virus (SFTSV). Although SFTS originated in China, it is an emerging infectious disease with prevalence confirmed in Japan, Korea, and Vietnam. The full-length genomes of 51 Korean SFTSV isolates from 2013 to 2016 were sequenced, and the sequences were deposited into a public database (GenBank) and analyzed to elucidate the phylogeny and evolution of the virus. Although most of the Korean SFTSV isolates were closely related to previously reported Japanese isolates, some were closely related to previously reported Chinese isolates. We identified one Korean strain that appears to have resulted from multiple inter-lineage reassortments. Several nucleotide and amino acid variations specific to the Korean isolates were identified. Future studies should focus on how these variations affect virus pathogenicity and evolution.

Colistin Resistance and Extensive Genetic Variations in PmrAB and PhoPQ in Klebsiella Pneumoniae Isolates from South Korea - Hae Suk Cheong; So Yeon Kim; Jungyu Seo; Yu Mi Wi; Kyong Ran Peck; Kwan Soo Ko (Current Microbiology, 2020)

Arabidopsis zinc finger homeodomain protein ZHD5 promotes shoot regeneration and confers other cytokinin-related phenotypes when overexpressed - Jin-Baek Kim; Jung-Youn Kang; Min Young Park; Mi-ran Song; Young Cheol Kim; Soo Young Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Characterization of PyGUS gene silencing in the red macroalga, Pyropia yezoensis - Yoon Ju Shin; Jong-Min Lim; Ji Hyun Park; Dong-Woog Choi; Mi Sook Hwang; Eun-Jeong Park; Sung Ran Min; Suk Weon Kim; Won-Joong Jeong (Plant Biotechnology Reports, 2016)

Effects of zinc oxide nanoparticle dispersants on cytotoxicity and cellular uptake - Mi-Rae Jo; Hae-Eun Chung; Hyun-Jin Kim; Song-Hwa Bae; Mi-Ran Go; Jin Yu; Soo-Jin Choi (Molecular & Cellular Toxicology, 2016)

Study of Photo and Thermoluminescence Properties to Identify Irradiated Dried-Fishery Products - Moon-Young Kim; Jae-Jun Ahn; Kashif Akram; Gui-Ran Kim; Mi-Seon Jeong; Ji-Young Kwak; Joong-Ho Kwon (Journal of Aquatic Food Product Technology, 2016)

Fermented Saccharina japonica (Phaeophyta) improves neuritogenic activity and TMT-induced cognitive deficits in rats - Hyun-Jung Park; Mi-Sook Lee; Hyun Soo Shim; Gyeong-Ran Lee; Sun Yong Chung; Young Mi Kang; Bae-Jin Lee; Yong Bae Seo; Kyung Soo Kim; Insop Shim (Algae, 2016)

Ethnobotany of the wild edible plants gathered in Ulleung Island, South Korea - Homervergel G. Ong; Jae-Min Chung; Hye-Ran Jeong; Young-Dong Kim; Kyung Choi; Chang-Ho Shin; You-Mi Lee (Genetic Resources and Crop Evolution, 2016)

Transcriptomic study of mouse embryonic neural stem cell differentiation under ethanol treatment - Chanchal Mandal; Ji Hyun Park; Mi Ran Choi; Sun Hwa Kim; Abimbola Comfort Badejo; Jin Choul Chai; Young Seek Lee; Kyoung Hwa Jung; Young Gyu Chai (Molecular Biology Reports, 2015)

Characterization and miRNA-mediated posttranscriptional regulation of vitelline membrane outer layer protein I in the adult chicken oviduct - Sang In Lee; Mi-Ran Ji; Ye-Jin Jang; Mi-hyang Jeon; Jeom Sun Kim; Jin-Ki Park; Ik-Soo Jeon; Sung June Byun (In Vitro Cellular & Developmental Biology - Animal, 2015)

Global Transcriptome Profiling of Genes that Are Differentially Regulated During Differentiation of Mouse Embryonic Neural Stem Cells into Astrocytes - Dalmuri Han; Mi Ran Choi; Kyoung Hwa Jung; Namshin Kim; Se kye Kim; Jin Choul Chai; Young Seek Lee; Young Gyu Chai (Journal of Molecular Neuroscience, 2015)

Role of vacuolating cytotoxin VacA and cytotoxin-associated antigen CagA of Helicobacter pylori in the progression of gastric cancer - Mi-Ran Ki; Meeyul Hwang; Ah-Young Kim; Eun-Mi Lee; Eun-Joo Lee; Myeong-Mi Lee; Soo-Eun Sung; Sang-Hyeob Kim; Hye Seung Lee; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2014)

Silk fibroin based hydrogel for regeneration of burn induced wounds - Hyung Woo Ju; Ok Joo Lee; Bo Mi Moon; Faheem A. Sheikh; Jung Min Lee; Jung-Ho Kim; Hyun Jung Park; Dong Wook Kim; Min Chae Lee; Soo Hyeon Kim; Chan Hum Park; Hae Ran Lee (Tissue Engineering and Regenerative Medicine, 2014)

ENA-A actimineral resource A extends lifespan associated with antioxidant mechanism in SMP30 knockout mice - Jung-Youn Han; Meeyul Hwang; Sung-Yong Hwa; Jin-Kyu Park; Mi-Ran Ki; Il-Hwa Hong; Ah-Young Kim; Eun-Mi Lee; Eun-Joo Lee; Chang-Woo Min; Kyung-Ku Kang; Myeong-Mi Lee; et al. (Molecular and Cellular Biochemistry, 2014)

Resveratrol relieves hydrogen peroxide-induced premature senescence associated with SIRT1 in human mesenchymal stem cells - Mi Ran Choi; Dal Mu Ri Han; Sun Hwa Kim; Takbum Ohn; Kyoung Hwa Jung; Young Gyu Chai (Molecular & Cellular Toxicology, 2014)

Functional Analysis of Histone Demethylase Jmjd2b on Lipopolysaccharide-Treated Murine Neural Stem Cells (NSCs) - Nando Dulal Das; Mi Ran Choi; Kyoung Hwa Jung; Ji Hyun Park; Hyung Tae Lee; Amitabh Das; Seung Hyun Kim; Young Gyu Chai (Neurotoxicity Research, 2013)

Effects of pargyline on cellular proliferation in human breast cancer cells - Hyung Tae Lee; Kyoung Hwa Jung; Se Kye Kim; Mi Ran Choi; Young Gyu Chai (Molecular & Cellular Toxicology, 2012)

Identification of genes induced by Venturia nashicola in indigenous Korean pear ‘Hwangsilri’ - Il Sheob Shin; Kyung Mi Bae; Ga Young Nam; Byoung-Cheorl Kang; Jaean Chun; Kang Hee Cho; Se Hee Kim; Hyung Seok Choi; Hyun Ran Kim; Hae Sung Hwang; Hee Jae Lee (Horticulture, Environment, and Biotechnology, 2012)

Real-time detection of cellular apoptosis using a rat C6 glioma cell-based assay system - Kyoung Hwa Jung; Young Me Song; Nando Dulal Das; Kyoung Sun Park; Mi Ran Choi; Sang Youn Hwang; Eun Kyu Lee; Moon Kwon Lee; Jaebum Choo; Kyoung Suk Kim; Moo Soung Kim; Sang Rin Lee; et al. (Molecular & Cellular Toxicology, 2011)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Gilvimarinus agarilyticus sp. nov., a new agar-degrading bacterium isolated from the seashore of Jeju Island - Byung-Chun Kim; Mi Na Kim; Kang Hyun Lee; Hyun Soon Kim; Sung Ran Min; Kee-Sun Shin (Antonie van Leeuwenhoek, 2011)

Putative probiotic Lactobacillus spp. from porcine gastrointestinal tract inhibit transmissible gastroenteritis coronavirus and enteric bacterial pathogens - Rejish Kumar V. J; Byeong Joo Seo; Mi Ran Mun; Chul-Joong Kim; Insun Lee; Hongik Kim; Yong-Ha Park (Tropical Animal Health and Production, 2010)

High-level expression of a human β-site APP cleaving enzyme in transgenic tobacco chloroplasts and its immunogenicity in mice - Jung Won Youm; Jae Heung Jeon; Hee Kim; Sung Ran Min; Mi Sun Kim; Hyouk Joung; Won Joong Jeong; Hyun Soon Kim (Transgenic Research, 2010)

Bile tolerant Lactobacillus reuteri isolated from pig feces inhibits enteric bacterial pathogens and porcine rotavirus - Byeong Joo Seo; Mi Ran Mun; Rejish Kumar V. J; Chul-Joong Kim; Insun Lee; Young-Hyo Chang; Yong-Ha Park (Veterinary Research Communications, 2010)

An atypical soybean leucine-rich repeat receptor-like kinase, GmLRK1, may be involved in the regulation of cell elongation - Sunghan Kim; Su-Jin Kim; Yun-Jeong Shin; Ji-Hye Kang; Mi-Ran Kim; Kyoung Hee Nam; Myeong-Sok Lee; Suk-Ha Lee; Yul-Ho Kim; Soon-Kwan Hong; Desh Pal S. Verma; Jong-Yoon Chun; et al. (Planta, 2009)

Specific accumulation of heavy metals in squid collected from offshore Korean waters: preliminary results for offshore biomonitoring and food safety assessment - Gi Beum KIM; Mi Ran KANG; Jae Won KIM (Fisheries Science, 2008)

ATHB23, an Arabidopsis class I homeodomain-leucine zipper gene, is expressed in the adaxial region of young leaves - Yun-Kyoung Kim; Ora Son; Mi-Ran Kim; Kyoung-Hee Nam; Gyung-Tae Kim; Myeong-Sok Lee; Soon-Young Choi; Choong-Ill Cheon (Plant Cell Reports, 2007)

Effects of bio-active ceramic resources in cutaneous wound healing and the role of TGF-β signaling - Jae-Yong Chung; Sun Hee Do; Won-Il Jeong; Da-Hee Jeong; Sang-Joon Park; Mi-Ran Ki; Dong-Mi Kwak; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Up-regulation of Metabotropic glutamate receptor 3 (mGluR3) in rat fibrosis and cirrhosis model of persistent hypoxic condition - Sun Hee Do; Hae-Sun Yun; Won-Il Jeong; Da-Hee Jeong; Mi-Ran Ki; Jae-Yong Chung; Sang-Joon Park; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Alcohol-induced bone degradation and its early detection in the alcohol-fed castrated rats - Sun Hee Do; Won Il Jeong; Da Hee Jeong; Mi-Ran Ki; In-Seon Lee; Dong-Mi Kwak; Tae Hwan Kim; Yoo Kyeong Kim; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2006)

Expression of tobacco cDNA encoding phytochelatin synthase promotes tolerance to and accumulation of Cd and As inSaccharomyces cerevisiae - Young Jin Kim; Kwang Seok Chang; Mi Ran Lee; Jong Hoon Kim; Chang Eun Lee; Yoon Joo Jeon; Jong Soon Choi; Hyoung Sun Shin; Seongbin Hwang (Journal of Plant Biology, 2005)

Anti-fungal effects of phenolic amides isolated from the root bark of Lycium chinense - Dong Gun Lee; Yoonkyung Park; Mi-Ran Kim; Hyun Jun Jung; Young Bae Seu; Kyung-Soo Hahm; Eun-Rhan Woo (Biotechnology Letters, 2004)

A taxonomic study onPediastrum boryanum meneghini in Korea - Chang Yoon Kyung; Mi Ran Kim (Journal of Plant Biology, 1997)